2006
DOI: 10.1007/s10038-005-0351-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Snurf–Snrpn IC transcript in the oocyte and its putative role in the imprinting establishment of the mouse 7C imprinting domain

Abstract: The human chromosome 15q11-q13, or mouse chromosome 7C, is an imprinting domain controlled by bipartite imprinting centers (ICs): Prader-Willi syndrome (PWS)-IC and Angelman syndrome (AS)-IC. PWS-IC functions to maintain the paternal epigenotype on the paternal chromosome in somatic cells, while AS-IC plays a role in the establishment of the maternal epigenetic mark at PWS-IC in the female germline or early embryos. Several alternative exons and promoters of Snurf-Snrpn (SNRPN upstream reading frame-small nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…Instead, the mouse has nine highly repeated upstream promoters located over 530 kb (31). Although all nine repeats are unlikely to be active promoters, it is clear that some are used in both oocytes and somatic cells (10,(18)(19)(20)32). Removal of the three proximal promoters leads to a weak partial imprinting defect, consistent with functional complementation by the remaining upstream promoters (33).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Instead, the mouse has nine highly repeated upstream promoters located over 530 kb (31). Although all nine repeats are unlikely to be active promoters, it is clear that some are used in both oocytes and somatic cells (10,(18)(19)(20)32). Removal of the three proximal promoters leads to a weak partial imprinting defect, consistent with functional complementation by the remaining upstream promoters (33).…”
Section: Discussionmentioning
confidence: 96%
“…Although lacking sequence homology, the mouse Snrpn locus also contains several upstream promoter exons that are alternatives to body exon 1 (10,18). These transcripts become detectable in mouse oocytes just before the application of DNA methylation at the PWS-IC (19,20). Using BAC transgenes containing both mouse Snrpn upstream and body exons, we recently demonstrated that these oocyte transcripts transiting the PWS-IC are necessary and sufficient to observe both DNA methylation at the PWS-IC and imprinted Snrpn expression (20).…”
mentioning
confidence: 99%
“…2,7 This hypothesis is supported by the work of Chotalia et al, 8 who found that transcription is required for the establishment of germlinemethylation marks at imprinted genes. On the other hand, transgene experiments in which the 880 bp AS-SRO was found to be sufficient for silencing the SNURF -SNRPN promoter seem to argue against this hypothesis.…”
Section: Introductionmentioning
confidence: 79%
“…Studies on the mouse chromosome 7C, which is the homolog of human 15q11-q13, have shown that expression of its imprinting center transcript is abundant in the brain and in the ovary, particularly in oocytes and granulosa cells of the secondary and developing follicles, while no expression was found in other tissues (40). Other studies in the mouse suggest that loss of the necdin gene in chromosome 7C may result in impaired development of GnRH neurons (41).…”
Section: Discussionmentioning
confidence: 99%